2015
DOI: 10.1051/fruits/2014041
|View full text |Cite
|
Sign up to set email alerts
|

The arbuscular mycorrhiza fungusRhizophagus irregularisMUCL 41833 decreases disease severity of Black Sigatoka on banana c.v. Grande naine, underin vitroculture conditions

Abstract: Introduction. Mycosphaerella fijiensis, the fungal pathogen causing Black Sigatoka disease, attacks almost all cultivars of bananas and plantains. Currently, the repeated application of fungicides is the most widespread control measure, while the use of bio-control agents remains almost ignored. Here we investigated, under in vitro culture conditions, whether an arbuscular mycorrhizal fungus (AMF-Rhizophagus irregularis MUCL 41833) could reduce the severity of disease caused by M. fijiensis MUCL 47740 on banan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Rhizophagus irregularis (Błaszk., Wubet, Renker & Buscot) C. Walker & A. Schüßler 2010 (former Glomus intraradices) is an obligate biotrophic arbuscular mycorrhizal fungus that belongs to phylum: Mucoromycota, subphylum: Glomeromycotina, class: Glomeromycetes [8], and forms mutualistic symbioses with various plant species [9]. Several beneficial effects have been widely reported as a result of this relationship, including the enhancement of plant growth, nutrient and water transport, improvement of heavy metal, salinity, and drought tolerance, and the induction of plant disease resistance [10][11][12][13]. In this regard, El-Sharkawy et al [14] reported a significant reduction in the stem rust of wheat, which is caused by Puccinia graminis Pers.…”
Section: Introductionmentioning
confidence: 99%
“…Rhizophagus irregularis (Błaszk., Wubet, Renker & Buscot) C. Walker & A. Schüßler 2010 (former Glomus intraradices) is an obligate biotrophic arbuscular mycorrhizal fungus that belongs to phylum: Mucoromycota, subphylum: Glomeromycotina, class: Glomeromycetes [8], and forms mutualistic symbioses with various plant species [9]. Several beneficial effects have been widely reported as a result of this relationship, including the enhancement of plant growth, nutrient and water transport, improvement of heavy metal, salinity, and drought tolerance, and the induction of plant disease resistance [10][11][12][13]. In this regard, El-Sharkawy et al [14] reported a significant reduction in the stem rust of wheat, which is caused by Puccinia graminis Pers.…”
Section: Introductionmentioning
confidence: 99%
“…Increased biomass was often reported in banana plants colonized by AMF (Declerck et al, 1995; Oye Anda et al, 2015). This increase was usually attributed to the capacity of the extraradical AMF mycelium network to take up, translocate and transfer high amounts of nutrients (e.g., P) to the host plant cortical cells via arbuscules in exchange for photosynthates.…”
Section: Discussionmentioning
confidence: 99%
“…The strain was then transferred onto V8 juice agar medium (Erwin and Ribeiro, 1996) in Petri plates (90 mm diam.) for another 2 weeks under continuous light (PPF of 60–65 μmol m -2 s -1 ) at 22°C for mycelium and spores production (Oye Anda et al, 2015). The mycelium was then scrapped from the culture medium, grinded in 10 ml of sterile water with a mortar and pestle and passed through sterile cheesecloth (one-layer pore size of approximately 150 μm) to separate the mycelium from conidia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased resistance was observed in tomato against Alternaria solani (Fritz et al, 2006) and Botrytis cinerea (Jung et al, 2009); in cucumber against Colletotrichum orbiculare (Lee et al, 2005) and in potato against Phytophthora infestans (Gallou et al, 2011). Recently, Oye Anda et al, (2015) demonstrated under in vitro culture conditions that pre-mycorrhized banana (cv. Grande naine) plantlets had reduced leaf-spot disease symptoms caused by M. fijiensis compared to non-mycorrhized plants.…”
Section: Introductionmentioning
confidence: 99%